Observation and modeling of atmospheric OH and HO2∗ radicals at a subtropical rural site and implications for secondary pollutants - Z. Zou; T. Chen; Q. Chen; W. Sun; S. Han; Z. Ren; X. Li; W. Song; A. Ge; Q. Wang; X. Tian; C. Pei; et al. (Atmospheric Chemistry and Physics)
HOx radicals (OH and HO2) are crucial oxidants that determine atmospheric oxidation capacity and the production of secondary pollutants; however, their sources and sinks remain incompletely understood in certain rural, forest, and maritime environments. This study measured <msubsup>HO2∗</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="23pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="16a5119f850650e91518d92f5e605c09"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-8147-2025-ie00004.svg" width="23pt" height="14pt" src="acp-25-8147-2025-ie00004.png"/></svg:svg> (HO2 + contribution from RO2, organic peroxyl radicals) and OH concentrations using a chemical ionization mass spectrometer at a subtropical rural site in southern China from 12 November to 19 December 2022. The average peak concentrations were 3.50 ± 2.47 × 106 cm−3 for OH and 1.34 ± 0.93 × 108 cm−3 for <msubsup>HO2∗</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="23pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="dc19ee8d3b1067dde070fac7e2890a95"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-8147-2025-ie00005.svg" width="23pt" height="14pt" src="acp-25-8147-2025-ie00005.png"/></svg:svg>. Model-estimated contribution from RO2 to HO2 during the measurement period ranged from 44 % to 69 % of <msubsup>HO2∗</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="23pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="7ea210efdc007f6cda21857ee3b28272"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-8147-2025-ie00006.svg" width="23pt" height="14pt" src="acp-25-8147-2025-ie00006.png"/></svg:svg>. Calculations based on an observation-constrained chemical model revealed an overestimation of HO2 and OH concentrations during warm periods of the field study. Sensitivity tests suggest that adding HOx sinks or an HO2 recycle process to the model could improve the model performance. Over-simulation of HOx in the model resulted in overestimations of midday (10:00–15:00 UTC) production rates by more than 79 % for ozone and a factor of 1.88 for nitric acid. Our study highlights the need for further improving understanding of the sources and sinks of OH and HO2 and representation of them in air quality models.